A thematic review of inclusive education research in South Africa - Seedat, Nasreen (My University, 2018)
Education White Paper 6 was developed with the aim of transforming the educational system of South Africa from one of exclusion of learners with disabilities to one that is more inclusive of all learners. This was to be done through the establishment of an integrated educational system that embraces children with barriers to learning into mainstream public schooling systems. This system should hold a flexible curriculum, structures to provide support for teachers and other schooling staff in implementing and maintaining the new inclusive system. The skills of teachers are to be improved so as to effectively manage classes wherein diverse ranges of learning needs are present. The primary aim of this research was to examine inclusive education research conducted in South Africa since its implementation in 2001. This was done through a systematic literature review analysis. Articles were selected for inclusion in the review based on the following criteria: the studies had to have been published in peer-reviewed journals between the years 2001 and 2016 to represent the extent of research on inclusive education in South Africa since its implementation. Studies had to be data based (either primary or secondary) and documented in English with a focus on inclusive education in South Africa. Studies had to meet all the inclusion criteria in order to be selected for inclusion into the review. Thirty seven eligible journal articles were included for the current review, of which 43% (n=16) used a qualitative methodology, 16% (n=6) used a mixed methods design and 6% (n=2) used a quantitative methodology. The remaining 35% (n=13) were conceptual articles. To obtain a thematic review of inclusive education research in South Africa Thomas and Harden’s thematic synthesis approach of data analysis was used. The results identified the following main emergent themes: Attitudes, beliefs, perceptions and practices of key stakeholders, Dissemination of information, Teacher training, Contextual factors, History, culture and traditions toward inclusive education, and Collaboration. Findings of the review clearly indicate that there are drawbacks and limitations as well as successes in relation to inclusive education implementation in South Africa. There are lessons to be learned from the South African experience of inclusive education in relation to the implementation of educational policy and the need for research to inform practice.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Education in Educational Psychology in the faculty of Humanities, University of the Witwatersrand, Johannesburg, 2018.
Keywords: Inclusive education--South Africa; Inclusive education--Research